Dibenzoate esters of cis‐tetralin‐2, 3‐diol as analogs of (–)‐epigallocatechin gallate: synthesis and crystal structure of anticancer drug candidates. Issue 12 (24th November 2020) - Rutherford, Ryan Noboru; Ura, Shinji; Chan, Tak-Hang; Fukumoto, Kozo; Nishioka, Takanori; Renzetti, Andrea
Abstract : Six synthetic analogs of (−)‐epigallocatechin gallate sharing a common tetralindiol dibenzoate core were synthesized and fully characterized. Abstract : (−)‐Epigallocatechin gallate (EGCG), the main component of green tea extract, displays multiple biological activities. However, it cannot be used as a drug due to its low cellular absorption, instability and metabolic degradation. Therefore, there is a need to provide analogs that can overcome the limitations of EGCG. In this work, six synthetic analogs of EGCG sharing a common tetralindiol dibenzoate core were synthesized and fully characterized by 1 H NMR, 13 C NMR, HRMS and IR spectroscopies, and X‐ray crystallography. These are (2 R, 3 S )‐1, 2, 3, 4‐tetrahydronaphthalene‐2, 3‐diyl bis[3, 4, 5‐tris(benzyloxy)benzoate], C66 H56 O10, and the analogous esters bis(3, 4, 5‐trimethoxybenzoate), C30 H32 O10, bis(3, 4, 5‐trifluorobenzoate), C24 H14 F6 O4, bis[4‐(benzyloxy)benzoate], C38 H32 O6, bis(4‐methoxybenzoate), C26 H24 O6, and bis(2, 4, 6‐trifluorobenzoate), C24 H14 F6 O4 . Structural analysis revealed that the molecular shapes of these dibenzoate esters of tetralindiol are significantly different from that of previously reported dimandelate esters or monobenzoate esters, as the acid moieties extend far from the bicyclic system without folding back over the tetralin fragment. Compounds with small fluorine substituents take a V‐shape, whereas larger methoxy and benzyloxy groups determine the formation of an L‐shape or a cavity. Intermolecular interactions are dominated by π–π stacking and C—H…π interactions involving the arene rings in the benzoate fragment and the arene ring in the tetrahydronaphthalene moiety. All six crystal structures are determined in centrosymmetric space groups (either P, P 21 / n, C 2/ c or I 2/ a ).